2019
DOI: 10.1101/gad.322602.118
|View full text |Cite
|
Sign up to set email alerts
|

NRDE2 negatively regulates exosome functions by inhibiting MTR4 recruitment and exosome interaction

Abstract: The exosome functions in the degradation of diverse RNA species, yet how it is negatively regulated remains largely unknown. Here, we show that NRDE2 forms a 1:1 complex with MTR4, a nuclear exosome cofactor critical for exosome recruitment, via a conserved MTR4-interacting domain (MID). Unexpectedly, NRDE2 mainly localizes in nuclear speckles, where it inhibits MTR4 recruitment and RNA degradation, and thereby ensures efficient mRNA nuclear export. Structural and biochemical data revealed that NRDE2 interacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 50 publications
12
41
0
Order By: Relevance
“…To determine how late transcripts avoid degradation at their proper time of expression, we centered our attention on the human n uclear R NAi- de fective 2 (NRDE2) protein. NRDE2 localizes to nuclear speckles where it forms a 1:1 complex with MTR4 to inhibit its recruitment and RNA degradation (54). Given this protective activity, we hypothesized that KSHV uses NRDE2 to protect late transcripts from degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine how late transcripts avoid degradation at their proper time of expression, we centered our attention on the human n uclear R NAi- de fective 2 (NRDE2) protein. NRDE2 localizes to nuclear speckles where it forms a 1:1 complex with MTR4 to inhibit its recruitment and RNA degradation (54). Given this protective activity, we hypothesized that KSHV uses NRDE2 to protect late transcripts from degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Our data show that the host factor NRDE2 is required for evasion of PPD during late infection (Fig 5). NRDE2 function is linked to its residence in nuclear speckles, where it interacts with MTR4 to inhibit its activity thereby protecting speckle-associated mRNAs (54). As expression of KSHV late genes occurs at the onset of viral genome replication, we speculate that NRDE2 re-localizes to replication compartments (Fig 6B).…”
Section: Discussionmentioning
confidence: 99%
“…This temporal regulation was linked to nuclear speckles and the host nuclear RNAi-defective 2 (NRDE2) protein. NRDE2 is a negative regulator of exosomes through the formation of complexes with MTR4, which leads to inhibition of exosome-mediated degradation [63]. During late replication, the viral replication compartment merges with nuclear speckles where NRDE2 resides, leading to the formation of NRDE2 interactions with MTR4, which prevents the assembly of the PPD-mediated exosome complex [55].…”
Section: Nuclear Decaymentioning
confidence: 99%
“…It has been proposed that mRNAs are shuttled through nuclear speckles for assembly into export‐ready mRNPs (Akef, Zhang, Masuda, & Palazzo, ; Dias, Dufu, Lei, & Reed, ; Mor et al, ). A recent report even suggested that to further outrun nuclear decay, exosome activity is inhibited in nuclear speckles through the negative regulation of MTR4 by the nuclear RNAi defective‐2 (NRDE2) protein (J. Wang, Chen, et al, ). That is, NRDE2 is not only enriched in nuclear speckles, but it also physically interacts with MTR4 to lock it in a 1:1 stoichiometry, which blocks key residues of MTR4 involved in its recruitment to capped RNAs via the CBCA as well as to the exosome (Figure ).…”
Section: Main Bodymentioning
confidence: 99%
“…That is, NRDE2 is not only enriched in nuclear speckles, but it also physically interacts with MTR4 to lock it in a 1:1 stoichiometry, which blocks key residues of MTR4 involved in its recruitment to capped RNAs via the CBCA as well as to the exosome (Figure ). This combinatorial inhibition is suggested to promote productive export of mRNAs by providing a decay‐free zone in nuclear speckles (J. Wang, Chen, et al, ).…”
Section: Main Bodymentioning
confidence: 99%